Content-expressive behavior and ideological extremity: An examination of the roles of emotional intelligence and information network heterogeneity. (February 2018) - Barnidge, Matthew; Ardèvol-Abreu, Alberto; Gil de Zúñiga, Homero
One thriving area of research on participatory media revolves around political expression and the creation of political content. This study analyzes the connections between these behaviors, heterogeneous information networks, and ideological extremity while accounting for the role of emotional intelligence. Results from a two-wave-panel survey of US adults show that people who engage in content-expressive behavior are embedded in heterogeneous information networks and that emotional intelligence moderates the relationship between content-expressive behavior and ideological extremity.